Impact of uPA/PAI-1 and disseminated cytokeratin-positive cells in breast cancer - Bruno Märkl; Martin Kazik; Nadia Harbeck; Elzbieta Jakubowicz; Reinhard Hoffmann; Thomas Jung; Dieter Steinfeld; Gerhard Schenkirsch; Günter Schlimok; Daniel Oruzio (BMC Cancer, 2019)
Abstract Background The protease uPA and its inhibitor PAI-1 play major roles in hemostasis and are also involved in cancer progression. This is mainly caused by their ability to degrade extracellular matrix-facilitating tumor cell migration. This study aimed to investigate the impact of uPA/PAI-1 and disseminated cytokeratin-positive cells (dCK+) on the outcome and the existence of synergistic effects. Methods We retrospectively analyzed a cohort of 480 breast cancer cases with known uPA/PAI-1 and dCK+ status. uPA/PAI-1 was tested on fresh tumor samples using a commercial ELISA test. Bone marrow aspirates were investigated immunocytochemically for CK18. Results DCK+ cells were identified in 23% of cases. uPA positivity was significantly associated with the occurrence of dCK+ cells (P = 0.028). uPA and PAI-1 were significantly associated with outcome in the subgroup of early-stage cases without chemotherapy. DCK+ cells alone were not prognostic. However, we found synergistic effects. In the subgroup of node-negative cases with and without chemotherapy, the prognostic impact of uPA and PAI-1 was enhanced in cases with additional dCK-positivity (triple +). In cases without chemotherapy, triple-positive status was independently prognostic (HR: 9.3 CI: 1.1–75) next to T stage. Conclusions uPA and PAI-1 seem to influence the metastatic potential of dCK+ cells, which underlines its important role in tumor progression.